Podobe modernosti v prvencu Janka Silana Čuki - Príhodová, Edita (Slavia Centralis, 2020)
The Image of Modernity in Janko Silan’s Čuki In the history of Slovak literature, Janko Silan is a well-known poet of Slovak Catholic modernism and spiritual poetry. This article outlines an interpretation of his debut collection, Kuvici. Silan’s use of figurative language and the stylizations of his lyric subject reveal that he was inspired by the poetics of Slovak, Czech, and French modernism. We can categorize his style as a symbolic, sometimes decadent, modernism. Silan used motifs from folklore. He created an unique original poetic world in the centre of which is depicted the problematic nature of human life.